Critical Discourse Analysis of Sekufu Phenomenon in Family Resilience in Sangtandung Village, Luwu Regency - Nada Kamal; Andi sukmawati assaad; Anita Marwing (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study examines the phenomenon of sekufu (equality/conformity) in the context of family resilience in Sangtandung Village, Luwu Regency, through a discourse analysis approach. Sekufu is a crucial concept in marriage, encompassing equality in religious, educational, economic, and socio-cultural aspects. The research question examines how the discourse of sekufu is understood and practiced by the people of Sangtandung Village and its impact on family resilience amidst contemporary social dynamics. The research method employed a qualitative approach with critical discourse analysis techniques to uncover the meanings, practices, and ideologies underlying the community's understanding of sekufu. Data were collected through in-depth interviews, participant observation, and documentation with married couples, religious leaders, and community leaders in Sangtandung Village The research results show that community understanding of sekufu varies, ranging from traditional interpretations emphasizing equality of social and economic status to more flexible modern understandings. The practice of sekufu in partner selection is strongly influenced by local cultural values, religious teachings, and the community's socioeconomic conditions. It was found that the proper application of sekufu principles contributes positively to family resilience, reflected in harmonious husband-wife relationships, minimal family conflict, and household economic stability. This study recommends the importance of comprehensive premarital education on the concept of sekufu that balances traditional values with modern needs, as well as the role of religious and community leaders in providing a wise understanding to the younger generation regarding the importance of equality in building family resilience.